EXPLORING THE UNIQUE ASPECTS OF PROFESSIONAL DEVELOPMENT IN MILITARY EDUCATION: CONCEPTS AND IMPLICATIONS - Kudrat Khudaybergenov Bakhtiyorovich (American Journals, 2024)
Vocational skills play an important role in the formation of skills, abilities and qualifications of students receiving military education. This scientific article highlights the specific aspects that contribute to the successful professional development of students engaged in military education. Through a comprehensive analysis of existing research and an examination of the unique challenges and demands these individuals face, this study identifies key components necessary to enhance professional growth, develop leadership and critical thinking skills, and achieve overall success in military education programs. focused on lighting.